2019
DOI: 10.1371/journal.pbio.3000205
|View full text |Cite
|
Sign up to set email alerts
|

The parietal operculum preferentially encodes heat pain and not salience

Abstract: Substantial controversy exists as to which part of brain activity is genuinely attributable to pain-related percepts and which activity is due to general aspects of sensory stimulation, such as its salience, or the accompanying arousal. The challenge posed by this question rests largely in the fact that pain per se exhibits highly intense but unspecific characteristics. These therefore should be matched by potential control conditions. Here, we used a unique combination of functional magnetic resonance imaging… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 62 publications
11
50
0
Order By: Relevance
“…Additionally, as SLN has been linked with autonomic processing 20 . SLN connectivity to the thalamus was increased following MANIP (see Figure 3) and the thalamic cluster spanned important nuclei for pain modulation -ventral lateral posterior (VLp), ventral posterior lateral (VPL), and medial dorsal (MD), as evident by overlay with the canonical Morel thalamus atlas in MNI space.…”
mentioning
confidence: 99%
“…Additionally, as SLN has been linked with autonomic processing 20 . SLN connectivity to the thalamus was increased following MANIP (see Figure 3) and the thalamic cluster spanned important nuclei for pain modulation -ventral lateral posterior (VLp), ventral posterior lateral (VPL), and medial dorsal (MD), as evident by overlay with the canonical Morel thalamus atlas in MNI space.…”
mentioning
confidence: 99%
“…In their study, a brain area would be considered to be preferentially responding to pain if it meets the following four criteria: (1) the effect of painful stimulation should be larger than that of nonpainful heat; (2) the effect of painful stimulation should be larger than that of saliencematched unpleasant sound; (3) the relationship of ratings and fMRI response should be stronger for painful heat than for nonpainful heat; and (4) the positive relationship of pain ratings and fMRI responses should be stronger for painful heat than for salience-matched unpleasant sound. They found that an area in the posterior parietal operculum satisfied all four criteria and thus showed a preference for pain processing [87]. This study made an important progress in identifying brain regions having a preferential role in pain processing by matching saliency between painful and non-painful stimuli.…”
Section: Univariate Comparisons Of Brain Responses Between Painful Anmentioning
confidence: 80%
“…In one study, Horing et al used skin conductance responses (SCRs) as a measure of stimulus saliency, and compared the fMRI responses to painful heat with saliency-unmatched non-painful heat and with saliency-matched unpleasant sound [87]. In their study, a brain area would be considered to be preferentially responding to pain if it meets the following four criteria: (1) the effect of painful stimulation should be larger than that of nonpainful heat; (2) the effect of painful stimulation should be larger than that of saliencematched unpleasant sound; (3) the relationship of ratings and fMRI response should be stronger for painful heat than for nonpainful heat; and (4) the positive relationship of pain ratings and fMRI responses should be stronger for painful heat than for salience-matched unpleasant sound.…”
Section: Univariate Comparisons Of Brain Responses Between Painful Anmentioning
confidence: 99%
“…In contrast, the gradual learning of stimulus-value associations over multiple experiences is known to involve systems including the dopaminergic midbrain, striatum, insula, and amygdala (Schultz et al, 1997;LeDoux, 2000;Seymour and al., 2004;Schiller et al, 2008). In the case of learning from aversive stimuli such as heat, a network of regions including the insula and secondary somatosensory cortex respond to pain Apkarian et al, 2005;Tracey and Mantyh, 2007;Roy et al, 2014;Horing et al, 2019), suggesting a potential substrate for memory for the value of pain.…”
Section: Introductionmentioning
confidence: 99%